THE USE OF WEB 2.0 TOOLS IN ENGLISH LANGUAGE TEACHING IN SCHOOL - Kenzhebay Balzhan; Kudaibergenova M.R (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
In the conditions of informatization and computerization of the life of modern society and the strengthening of the role of information and communication technologies (ICT) in ensuring educational processes, the strategic orientation and priorities of the education system in various subject areas, including a foreign language, are radically changing.